Žaljive objave na družbenih omrežjih kot moderni izziv sodišč - Jereb, Ana (Pravni letopis, 2020)
When dealing with defamation on social media, courts try to follow the development and popularity of this new means of social interaction. The article focuses on foreign and domestic defamation cases regarding the social media. This case law distinguishes four different elements: (1) Does the freedom of speech protect posts on social media and against whom? (2) What is the right context of a certain social media post? (3) Could the use of symbols "like", "emoji" and others invoke liability? (4) How can a defamed individual effectively protect his or her rights in court? A "reasonable user" of social networks is different from the reader of written media. The meaning of a particular post can only be determined by considering its verbal and social context. The mere sharing of the post, its liking and even the use of a hashtag or emotion can form a basis for liability. In addition to the claim for damages, the target of defamation has the possibility to request the removal of the post from the author of the publication or from the social network provider.
Keywords: človekove pravice; družbena omrežja; obrekovanje; razžalitve; sodna praksa; svoboda govora